Menanamkan Akhlak Terpuji Sejak Dini Demi Mencegah Bullying - Chairul Fajar Tafrilyanto; Ema Surahmi; Septi Dariyatul Aini; M. Tauhed Supratman; Farhatun Farhatun (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This article discusses the importance of instilling good morals from an early age as an effective strategy to prevent bullying among children and teenagers. Bullying has become a serious problem in society, which can have a detrimental impact on the psychological and emotional well-being of those involved. In an effort to overcome this problem, this article explains how strong and consistent moral education from a young age can form positive values such as empathy, respect for differences, and social responsibility. The author discusses various methods for integrating moral education in formal and non-formal education curricula, as well as the role of parents and teachers in supporting children's moral development. Apart from that, this article also highlights the long-term benefits of moral education, such as reducing bullying incidents, creating a safer school environment, and forming a more socially conscious generation.Thus, this article emphasizes that instilling good morals from an early age is not just about preventing bullying, but also about creating a strong moral foundation for a better future for children and society as a whole.